Role of Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) in Cancer Prevention and Cancer Promotion - Rebecca S. Y. Wong (Advances in Pharmacological Sciences)
The nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly prescribed by medical practitioners in many clinical conditions for the symptomatic treatment of pain and fever. Due to their anti-inflammatory properties, these drugs have been investigated for their anticancer effects in numerous studies. This is because chronic inflammation has long been linked to carcinogenesis. As such, anti-inflammatory drugs are believed to play a role in cancer treatment and prevention. In the past few decades, research has shown that NSAIDs may decrease the risk of certain types of cancer. However, there is also a growing body of research that proves the contrary. Furthermore, NSAIDs are well known for many side effects, including some life-threatening ones. This review will discuss the relationship between chronic inflammation and cancer, the role of NSAIDs in cancer prevention and cancer promotion, and some of the potentially lethal side effects of these drugs.